Kinetics of Chlorination of o-Acetotoludide in Aqueous Solution by Molecular Chlorine - B. Patil, Dilip; Kshirsagar, A. (Asian Journal of Chemistry, 2016)
Kinetics of chlorination of o-acetotoludide by molecular chlorine in aqueous medium has been studied by employing the conventional technique. The specific reaction rate has been evaluated and found to be 1.88 m–1 s–1 at 25°C. Similar reaction rate determinations have been carried out at temperatures 30°, 35° and 40°C. The energy of activation, frequency factor and entropy of activation for the reaction has been evaluated and found to be 47.86 kJ mol–1, 4.91 × 108 m–1 s–1 and –87.0 kJ mol–1 respectively.